Follicular development and endometrial receptivity of different androgen phenotypes in women with polycystic ovary syndrome - Wen, Xinling; Wang, Li; Lv, Shulan (Frontiers in Endocrinology, 2024)
Objective: Polycystic ovary syndrome (PCOS) is an important reason of infertility in reproductive-aged women. Hyperandrogenism (HA) plays an important role in the pathogenesis of PCOS. This study was conducted to explore the follicular development and endometrial receptivity of different androgen phenotypes in reproductive-aged patients with PCOS. Methods: Two hundred and sixty-eight PCOS patients with infertility were recruited and divided into two groups according to different androgen phenotypes in this study: abnormal menstruation and hyperandrogenism (AM-HA group, n=127), abnormal menstruation and polycystic ovarian morphology (AM-PCOM group, n=141). The follicular development, endometrial receptivity, pregnancy rate and live birth rate during the natural menstrual cycle were compared between the two groups. Results: The number of dominant follicles, number of ovulations, and normal ovulation rate in AM-HA group were significantly lower compared with AM-PCOM group (P < 0.05). The endometrial thickness (ET), endometrial volume (EV), vascularization index (VI), flow index (FI) and vascularization flow index (VFI) on days from 14 to 24 of the menstrual cycle before ovulation were significantly lower in AM-HA group than in AM-PCOM group (P < 0.05). The endometrial VI, FI and VFI, the integrin αvβ3 and VEGF concentrations in uterine fluid during the implantation window were significantly lower in AM-HA group compared with AM-PCOM group (P < 0.05). However, no statistically significant differences were observed in the uterine artery blood flow parameters, ET and EV between the two groups (P > 0.05). The biochemical pregnancy rate, clinical pregnancy rate, ongoing pregnancy rate and live birth rate in AM-HA group were significantly lower compared with AM-PCOM group (P < 0.05). Conclusion: PCOS patients with phenotype of AM-HA were vulnerable to ovulation disorders and impaired endometrial receptivity, which resulted in reduced pregnancy rate. Treatment with HA is likely to become an effective approach for improving endometrial receptivity and fecundity disorders in patients with PCOS.